2016
DOI: 10.4103/0973-1296.186341
|View full text |Cite
|
Sign up to set email alerts
|

Antifatigue effects of ethanol extracts and polysaccharides isolated from Abelmoschus esculentus

Abstract: Background:The aim of this study is to determine the antifatigue active fraction from Abelmoschus esculentus. The in vivo antifatigue effects of ethanol extracts and polysaccharides from A. esculentus fruit have been determined. The polysaccharides of A. esculentus were determined as the best effective fractions of antifatigue effects.Materials and Methods:About 360 Kunming male mice were randomly divided into nine subgroups: normal control subgroup, model subgroup, positive subgroup and the ethanol extracts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Previous studies have attempted to identify antifatigue polysaccharides to delay fatigue and accelerate the elimination of tiredness. CS-hEPS showed better effects of relieving fatigue (64.62%) than Abelmoschus esculentus EPS (30.5%) [53]. ese effects are similar to Gynostemma pentaphyllum polysaccharide (GPP) which significantly prolonged exhaustive exercise time of mice.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Previous studies have attempted to identify antifatigue polysaccharides to delay fatigue and accelerate the elimination of tiredness. CS-hEPS showed better effects of relieving fatigue (64.62%) than Abelmoschus esculentus EPS (30.5%) [53]. ese effects are similar to Gynostemma pentaphyllum polysaccharide (GPP) which significantly prolonged exhaustive exercise time of mice.…”
Section: Discussionmentioning
confidence: 83%
“…In addition oral treatment with CS-hEPS increased the exercise tolerance, boosted the HG level by activating the energy metabolism, and reduced the accumulation of SUN and LDH contents during exercise, which could prolong the exercise durability. Due to the particularities of its chemical structure, CS-hEPS showed better antifatigue effects than those of previously reported polysaccharides [33,53,54,58]. e antitumor activity of CS-hEPS has also been tested against two types of cancer cell lines, myelogenous leukemia K562 and liver cancer Hep G cells, at different incubation periods and doses using 5-fluorouracil molecule (5-FU) as a positive control.…”
Section: Discussionmentioning
confidence: 96%
“…The ethanol extracts and polysaccharides of okra have antifatigue effects. 53 In line with this, okra seeds were the antifatigue part of okra pods; this is caused by reducing the levels of blood lactic acid and urea nitrogen and enhancing hepatic glycogen storage. 54 This study found that the consumption of okra makes pregnant women healthy, and is used to increase their life expectancy.…”
Section: Open Accessmentioning
confidence: 90%
“…Flowers during April-May. Pharmacological properties and functions: Anti-fatigue (Li et al 2016); antidiabetic, and antihyperlipidemic activities (Sabitha et al 2011).…”
Section: Medicinal Usementioning
confidence: 99%